Decision Support System Location of Development Center Using Promethee Method - Meyti Eka Apriyani; Indra Dharma Wijaya; Kiky Andy Wahyu (Nusantara Science and Technology Proceedings, 2022)
When deciding where to sell souvenirs, a city takes into account many criteria to improve its added value in the future. The process of identifying crucial factors to consider when choosing a site is completed. Land area, distance from trading operations, proximity to public transportation, proximity to tourist sites, and traffic flow are some of these criteria. It is required to utilize a decision support system to choose the location of the development for the souvenir center based on this choice. The location of development can be determined using this method using a variety of variables. A ranking of many alternative places is what this system produces. so that a city might use it as a guide when figuring out where to put the center for souvenir development. The Preference Ranking Organizational Method for Enrichment Evaluation is one of the techniques used in deciding where to build the souvenir center (PROMETHEE). In multi-criteria analysis, PROMETHEE is a technique for establishing the hierarchy. The PROMETHEE approach can be used to make decisions in the areas of marketing, human resources, site selection, and other areas involving alternative selection.